Finding “appeal” factors in local animation character design: formalistic and visual semiotic analysis (FVSA) - Teddy Marius Soikun; Ag. Asri Ag. Ibrahim (Intitut Seni Budaya Indonesia (ISBI) Bandung, 2021)
This research aims to understand the ‘appeal’ factor in local animated character design. ‘Appeal’ is one of the 12 principles of animation design and is often considered ambiguous. To achieve ‘appeal,’ one of the methods used is Viewer’s Impression Words (VIW), which is a modification of Kansei Words (KW). This method combines formalistic theory and visual semiotic to achieve Viewer’s Impression Words (VIW), an essential part of Kansei Engineering. The results of this experiment, it can be concluded that this method is able to help the participants choose the appropriate VIW word and towards the next activity that is the process of loose principles. This method is suggested as a new technique to improve the process in obtaining VIW or Kansei Words to use in the measurement exercises to find the affect (emotion) in understanding ‘appeal.’ This is to achieve loose principles in local animated character design.